Heat exchange rates between adult sockeye salmon ( Oncorhynchus nerka ) and the environment - Avery Dextrase; David A. Patterson; Eduardo G. Martins (Journal of Fish Biology, 2026)
Body temperatures of salmon do not always match the temperatures of their immediate environment. We investigated the relationship between varying ambient water temperatures and body temperatures of adult sockeye salmon Oncorhynchus nerka using Newton's law of cooling and non‐linear mixed models. The median estimated coefficient of heat exchange for O. nerka in this study was 0.09 min −1 with corresponding temperature change halftime and thermal time constant values of 7.7 and 11.1 min, respectively. There was little support for salmon condition factor and mass impacting , or differences in when the body was cooling or warming. Metabolically produced heat had a very small effect on body temperature. The bodies of the salmon did not instantaneously equilibrate with ambient temperatures. Model‐averaged predictions showed that it would take approximately 60 min for the core body temperature of an adult O. nerka to equilibrate with ambient temperature (i.e., rate of body temperature change −1 ) after moving into water temperatures 10°C cooler or warmer than their initial body temperature. Greater differences in body and ambient temperatures were predicted when the salmon experienced rapid and larger changes in ambient temperature. The differences in body and ambient temperatures experienced by Babine Lake O. nerka in this study highlight a need to exhibit caution when equating water temperature to the body temperature of fish in thermally heterogeneous environments across short timescales. The estimated values of and from this study could be applied to other research requiring body temperature predictions for free‐ranging adult O. nerka or possibly other similarly sized and shaped salmonids without using internal temperature loggers.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Laryngectomy Education and Training Resources: An Environmental Scan of Resources - Laura-Jayne Watson; Emer Fahy; David W. Hamilton; Linda Sharp; Vicky Thornton; Joanne M. Patterson (Journal of Cancer Education, 2026)
In many settings, head and neck cancer (HNC) services are centralized in large hospitals, meaning that community input from HNC specialists can be lacking. Community healthcare professionals often require laryngectomy-specific education and training to provide optimal care to people at home. However, laryngectomy-specific education/training is often sporadic and varies between centres, making it difficult to achieve standardisation in healthcare professionals’ laryngectomy knowledge and skills. This study aimed to identify and critically review existing laryngectomy education/training resources for healthcare professionals, which include elements applicable to community care. We used environmental scanning to systematically and comprehensively identify and examine all available education/training resources which had an element of education and/or training applicable to community laryngectomy care. Eligible resources were reviewed for training-specific details, laryngectomy-specific details, evaluation method, accessibility, and patient and public involvement (PPI). A total of 6655 resources were screened; 49 were eligible for data extraction. There was wide variability in the level of laryngectomy-specific content in the resources. PPI in development was lacking, and data detailing the impact of resources on healthcare professionals’ knowledge/skills and patient outcomes was sparse. This is the first study to systematically identify and appraise laryngectomy education/training resources which have applicability to community care. There is not one consistent approach to education/training development method, content, delivery, or evaluation, likely rendering these ineffective and lacking impact. Community-specific laryngectomy education and training, with clear implementation and evaluation, is required.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Quantifying changes in central Vietnam rainfall amount since the Late Pleistocene - Elizabeth W. Patterson; Alliya A. Akhtar; Michael L. Griffiths; David McGee; Quốc Đỗ-Trọng; Annabel Wolf; John A. Higgins; Stefania Gili; Mùi X. Trần; Hùng Q. Nguyễn; Trí H. Đinh; Thành N. Bùi; et al. (Earth and Planetary Science Letters, 2026)

Opportunity Knocks: Leveraging Offshore Wind Development as a Natural Experiment to Address the Ecological Function of Artificial Reefs - Raymond E. Czaja; Shayna A. Sura; William F. Patterson; David D. Chagaris; John F. Walter; Skyler R. Sagarese; Avery B. Paxton; William D. Heyman; Holden E. Harris (Fish and Fisheries, 2025)
Artificial structures deployed in marine environments as reefs are often presumed to increase fish production. However, our literature review found a lack of evidence, with only 12 studies empirically quantifying secondary production at artificial reefs, and only three studies using a control site. We propose the forthcoming large‐scale construction of offshore wind (OSW) energy structures presents a natural experiment to examine the ecological function of artificial reefs, including their effects on fish production. To provide causal inferences of OSW effects, studies must obtain appropriate ‘before’ data, per before‐after‐control‐impact and related designs. This requirement dictates that society must begin planning and collecting data now, prior to OSW deployment. We also highlight that responses beyond fish biomass measures, including life stage specific survival, site fidelity and trophic dynamics, must occur at appropriate spatial and temporal scales to maximise causal inference. By leveraging a timely opportunity and natural experiment with OSW development, the long‐running ‘attraction–production debate’ about artificial reef ecological function may be addressed.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Ontogenetic change in body shape for white sharks, Carcharodon carcharias , in Australian waters - Emily Hunt; Russell W. Bradford; David J. Booth; Cameron Doak; Toby A. Patterson; Victor M. Peddemors (Journal of Fish Biology, 2025)
The analysis of how biological shape changes across ontogeny can provide us with valuable information on how species adapt behaviorally, physiologically, and ecologically. The white shark Carcharodon carcharias is one of the largest and most widely distributed apex predators globally, yet an understanding of ontogenetic changes in body shape and relative scaling of length and weight measures is limited, especially in relation to foraging ecology. Through analysis of a suite of shape‐related metrics, we identified ontogenetic patterns of scaling throughout development. Isometric growth was exhibited for most metrics, failing to show a significant deviation from an isometric slope of 1.0 for length–length relationships, and 3.0 for weight–length relationships. The most notable difference from this trend was the negative allometric growth observed for the upper caudal‐fin lobe length, trunk length, and the mouth length. The surface area of the fins also presented a strong, positive relationship with precaudal length (PCL) and the girth at the pectoral fin. Negative allometric growth was exhibited for three of the fins (pectoral, upper caudal fin, and lower caudal fin) against PCL, exhibiting a significant deviation from the expected isometric growth of 2.0 for area–length relationships. There were no significant differences in morphometric relationships between geographic regions within Australia that samples were collected from. No differences between the sexes were identified; however, this may be an artifact of the lack of mature animal samples. Conversely, life stage was found to have a significant effect on the girth–length and weight–length relationships. The development of regression equations for morphometric measures allows the assessment of white shark body condition and may serve as an assessment tool to understand the potential impacts of human‐induced environmental change on white sharks.

Uncrewed surface vehicles in the Global Ocean Observing System: a new frontier for observing and monitoring at the air-sea interface - Ruth G. Patterson; Meghan F. Cronin; Sebastiaan Swart; Joana Beja; Johan M. Edholm; Jason McKenna; Jaime B. Palter; Alex Parker; Charles I. Addey; Wieter Boone; Paban Bhuyan; Justin J. H. Buck; et al. (Frontiers in Marine Science, 2025)
Observing air-sea interactions on a global scale is essential for improving Earth system forecasts. Yet these exchanges are challenging to quantify for a range of reasons, including extreme conditions, vast and remote under-sampled locations, requirements for a multitude of co-located variables, and the high variability of fluxes in space and time. Uncrewed Surface Vehicles (USVs) present a novel solution for measuring these crucial air-sea interactions at a global scale. Powered by renewable energy (e.g., wind and waves for propulsion, solar power for electronics), USVs have provided navigable and persistent observing capabilities over the past decade and a half. In our review of 200 USV datasets and 96 studies, we found USVs have observed a total of 33 variables spanning physical, biogeochemical, biological and ecological processes at the air-sea transition zone. We present a map showing the global proliferation of USV adoption for scientific ocean observing. This review, carried out under the auspices of the ‘Observing Air-Sea Interactions Strategy’ (OASIS), makes the case for a permanent USV network to complement the mature and emerging networks within the Global Ocean Observing System (GOOS). The Observations Coordination Group (OCG) overseeing GOOS has identified ten attributes of an in-situ global network. Here, we discuss and evaluate the maturation of the USV network towards meeting these attributes. Our article forms the basis of a roadmap to formalise and guide the global USV community towards a novel and integrated ocean observing frontier.

Oxidative gaseous air pollutant exposure interacts with PNPLA3-I148M genotype to influence liver fat fraction and multi-omics profiles in young adults - William B. Patterson; Nathan D. Young; Elizabeth A. Holzhausen; Frederick Lurmann; Donghai Liang; Douglas I. Walker; Dean P. Jones; Jiawen Liao; Zhanghua Chen; David V. Conti; Lida Chatzi; Jesse A. Goodrich; et al. (Environmental Pollution, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

The biodiversity of ice‐free Antarctica database - Aleks Terauds; Jasmine R. Lee; Hannah S. Wauchope; Ben Raymond; Dana M. Bergstrom; Peter Convey; Claire Mason; Charlotte R. Patterson; Sharon A. Robinson; Anton Van de Putte; David Watts; Steven L. Chown (Ecology, 2025)
Antarctica is one of Earth's most untouched, inhospitable, and poorly known regions. Although knowledge of its biodiversity has increased over recent decades, a diverse, wide‐ranging, and spatially explicit compilation of the biodiversity that inhabits Antarctica's permanently ice‐free areas is unavailable. This absence hinders both Antarctic biodiversity research and the integration of Antarctica in global biodiversity–related studies. Fundamental and applied research on biodiversity patterns, ecological structure and function, and options for conservation are reliant on spatially resolved, taxonomically consistent observations. Such information is especially important for modern, data‐driven biodiversity science, in both Antarctica and globally, and forms the backbone of biodiversity informatics, reflected, for example, in the Darwin Core Standard used by the Global Biodiversity Information Facility. Biodiversity data are also essential to fulfill the conservation requirements for Antarctica, as set out in the Protocol on Environmental Protection to the Antarctic Treaty and inform the design of systematic surveys to address biodiversity and ecological knowledge gaps, for both specific taxa and ecosystems. Such surveys are key requirements for understanding and mitigating the impacts of environmental change on the region's biodiversity. Here, we address these requirements through the public release of The Biodiversity of Ice‐free Antarctica Database. In 2008, we extracted a subset of biodiversity records only from terrestrial ice‐free areas from the Scientific Committee on Antarctic Research (SCAR) Antarctic Biodiversity Database. We have subsequently added thousands of records from a range of sources: checking, and where necessary (and possible), correcting the spatial location, clarifying, cross‐referencing, and harmonizing taxonomy with globally recognized sources, and documenting the original source of records. The Biodiversity of Ice‐free Antarctica Database spans the early 1800s to 2019 (with most records collected after 1950) and represents the most comprehensive consolidation of Antarctic ice‐free biodiversity occurrence data yet compiled into a single database. The Biodiversity of Ice‐free Antarctica Database contains 35,654 records of 1890 species in over 800 genera across six kingdoms and spans all Antarctic Conservation Biogeographic Regions. These data are released under a CC BY Attribution License ( http://creativecommons.org/licenses/by/4.0/ ).

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Drone-based monitoring and geomorphology of southern giant petrel nests near Palmer Station, western Antarctic Peninsula - Gregory D. Larsen; Hanna F. Varga; Donna L. Patterson-Fraser; David W. Johnston; Megan A. Cimino (Polar Biology, 2024)
Human activities and climate change threaten seabirds globally, and many species are declining from already small breeding populations. Monitoring of breeding colonies can identify population trends and important conservation concerns, but it is a persistent challenge to achieve adequate coverage of remote and sensitive breeding sites. Southern giant petrels ( Macronectes giganteus ) exemplify this challenge: as polar, pelagic marine predators they are subject to a variety of anthropogenic threats, but they often breed in remote colonies that are highly sensitive to disturbance. Aerial remote sensing can overcome some of these difficulties to census breeding sites and explore how local environmental factors influence important characteristics such as nest-site selection and chick survival. To this end, we used drone photography to map giant petrel nests, repeatedly evaluate chick survival and quantify-associated physical and biological characteristics of the landscape at two neighboring breeding sites on Humble Island and Elephant Rocks, along the western Antarctic Peninsula in January–March 2020. Nest sites occurred in areas with relatively high elevations, gentle slopes, and high wind exposure, and statistical models predicted suitable nest-site locations based on local spatial characteristics, explaining 72.8% of deviance at these sites. These findings demonstrate the efficacy of drones as a tool to identify, map, and monitor seabird nests, and to quantify important habitat associations that may constitute species preferences or sensitivities. These may, in turn, contextualize some of the diverse population trajectories observed for this species throughout the changing Antarctic environment.

Factors influencing cyanobacteria blooms: review of the historical monitoring data to assess management options for Lake Horowhenua - Max M. Gibbs; Jon Roygard; Maree Patterson; Logan Brown; David Brown (New Zealand Journal of Marine and Freshwater Research, 2024)
Factors influencing cyanobacterial blooms in Lake Horowhenua, Aotearoa/New Zealand, have been deduced from over 40 yrs routine monitoring data, detailed studies and high frequency (15‐min interval) data from an in‐lake monitoring buoy. Lake Horowhenua is currently hypertrophic but flips between a winter clear‐water, macrophyte dominated phase ( Potamogeton crispus), and a turbid phytoplankton dominated phase with substantial cyanobacterial ( Microcystis sp. ) blooms from mid‐summer to autumn. Nitrogen for growth comes from agriculture and horticulture via groundwater and spring‐fed streams. Phosphorus is released from the sediment when the weed beds die back. These nutrients stimulate the growth of Microcystis sp. , until the water temperature falls below 15°C. Microcystis sp can raise the pH to over 10, which releases P from the sediment, sustaining its growth. High pH transforms non‐toxic ammonium‐N released from the sediment to toxic unionised NH 3 , which may contribute to fish kills in summer/autumn. Management strategies cannot use P‐inactivation agents for cultural reasons and eradicating the macrophyte beds by spraying would cause the lake to permanently flip to a turbid state. Management of the macrophyte beds with a weed harvester is being trialled to allow a gradual replacement of P. crispus with indigenous species from the seed bank in the sediment.

Spatial distribution of selenium-mercury in Arctic seabirds - Marta Cruz-Flores; Jérémy Lemaire; Maud Brault-Favrou; Signe Christensen-Dalsgaard; Carine Churlaud; Sébastien Descamps; Kyle Elliott; Kjell Einar Erikstad; Alexey Ezhov; Maria Gavrilo; David Grémillet; Gaël Guillou; et al. (Environmental Pollution, 2024)

A Phase 2b Multicenter, Randomized, Double-Blind, Placebo-Controlled Study of OnabotulinumtoxinA for the Treatment of Upper Limb Essential Tremor: ELATE Trial in Progress - Richard Barbano; David Simpson; Katelin Patterson; Nabilah Alibhai; Lynn James (Toxicon, 2024)

Anaerobic Exercise and Recovery: Roles and Implications for Mortality in Pacific Salmon - Kim Birnie-Gauvin; David A. Patterson; Steven J. Cooke; Scott G. Hinch; Erika J. Eliason (Reviews in Fisheries Science & Aquaculture, 2023)

Automated remote sensing tools to counter illicit maritime activity: vessel detection, bathymetry and topography from WorldView imagery - Matthew J. McCarthy; David Hughes; Jeremy Patterson; Michael A. Channer; Michael McGee; Shannon Meade; Kenny Moss; Paul Trask (International Journal of Remote Sensing, 2023)

Using repeat injury assessments in adult sockeye salmon (Oncorhynchus nerka) to predict spawning success and describe severity of migration conditions - Madison A. Philipp; Kathryn S. Peiman; Glenn T. Crossin; Scott G. Hinch; David A. Patterson; Chris K. Elvidge; Steven J. Cooke (Fisheries Research, 2023)

Two new species of the genus Leptomyxa (Goodey, 1915) – Leptomyxa botanica n. sp. and Leptomyxa monrepos n. sp. from the soil habitats of Northwestern Russia - Nikita S. Kulishkin; Alexey V. Smirnov; David J. Patterson (European Journal of Protistology, 2023)

Evidence of population-level impacts and resiliency for Gulf of Mexico shelf taxa following the Deepwater Horizon oil spill - William F. Patterson; Kelly Lynn Robinson; Beverly K. Barnett; Matthew D. Campbell; David C. Chagaris; Jeffrey P. Chanton; Kendra L. Daly; David S. Hanisko; Frank J. Hernandez; Steven A. Murawski; Adam G. Pollack; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The goal of this paper was to review the evidence of population-level impacts of the Deepwater Horizon Oil Spill (DWH) on Gulf of Mexico (GOM) continental shelf taxa, as well as evidence of resiliency following the DWH. There is considerable environmental and biological evidence that GOM shelf taxa were exposed to and suffered direct and indirect impacts of the DWH. Numerous assessments, from mesocosm studies to analysis of biopsied tissue or tissue samples from necropsied animals, revealed a constellation of physiological effects related to DWH impacts on GOM biota, some of which clearly or likely resulted in mortality. While the estimated concentrations of hydrocarbons in shelf waters and sediments were orders of magnitude lower than measured in inshore or deep GOM environments, the level of mortality observed or predicted was substantial for many shelf taxa. In some cases, such as for zooplankton, community shifts following the spill were ephemeral, likely reflecting high rates of population turnover and productivity. In other taxa, such as GOM reef fishes, impacts of the spill are confounded with other stressors, such as fishing mortality or the appearance and rapid population growth of invasive lionfish ( Pterois spp.). In yet others, such as cetaceans, modeling efforts to predict population-level effects of the DWH made conservative assumptions given the species’ protected status, which post-DWH population assessments either failed to detect or population increases were estimated. A persistent theme that emerged was the lack of precise population-level data or assessments prior to the DWH for many taxa, but even when data or assessments did exist, examining evidence of population resiliency was confounded by other stressors impacting GOM biota. Unless efforts are made to increase the resolution of the data or precision of population assessments, difficulties will likely remain in estimating the scale of population-level effects or resiliency in the case of future large-scale environmental catastrophes.

Evaluation of Zoetis GeneMax Advantage genomic predictions in commercial Bos taurus Angus cattle - Brian.C. Arisman; Troy N. Rowan; Jordan M. Thomas; Harly J. Durbin; William R. Lamberson; David J. Patterson; Jared E. Decker (Livestock Science, 2023)

Metabolic constraints and individual variation shape the trade‐off between physiological recovery and anti‐predator responses in adult sockeye salmon - Michael J. Lawrence; Tanya S. Prystay; Melissa Dick; Erika J. Eliason; Chris K. Elvidge; Scott G. Hinch; David A. Patterson; Andrew G. Lotto; Steven J. Cooke (Journal of Fish Biology, 2023)
Metabolic scope represents the aerobic energy budget available to an organism to perform non‐maintenance activities ( e.g. , escape a predator, recover from a fisheries interaction, compete for a mate). Conflicting energetic requirements can give rise to ecologically relevant metabolic trade‐offs when energy budgeting is constrained. The objective of this study was to investigate how aerobic energy is utilized when individual sockeye salmon ( Oncorhynchus nerka ) are exposed to multiple acute stressors. To indirectly assess metabolic changes in free‐swimming individuals, salmon were implanted with heart rate biologgers. The animals were then exercised to exhaustion or briefly handled as a control, and allowed to recover from this stressor for 48 h. During the first 2 h of the recovery period, individual salmon were exposed to 90 ml of conspecific alarm cues or water as a control. Heart rate was recorded throughout the recovery period. Recovery effort and time was higher in exercised fish, relative to control fish, whereas exposure to an alarm cue had no effect on either of these metrics. Individual routine heart rate was negatively correlated with recovery time and effort. Together, these findings suggest that metabolic energy allocation towards exercise recovery ( i.e. , an acute stressor; handling, chase, etc. ) trumps anti‐predator responses in salmon, although individual variation may mediate this effect at the population level.

Evaluating the fidelity of enamel isotopic data and environmental variation in paleoecological studies: A case study in wild, known-aged, modern white-tailed deer (Odocoileus virginianus) - Taylor Malasek; Erin Barding; Michael J. Bender; Alexandra Bonham; Alfred J. Mead; Zachary Pilgrim; Patrick Powers; Jessica R. Patterson; David B. Patterson (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The Acceptability and Efficacy of a Virtual vs Hybrid Wellness Program on Health Outcomes Among Faculty and Staff Post COVID - Elizabeth Tenison; Henna Muzzafar; Julie Patterson; Joseph Ehrmann; David Sorkin; Diana Wind; Jeffrey Greeson; Carmen McDonald; Ciaran Cribbs; Jessica Gibb; David Zambriczki (Journal of Nutrition Education and Behavior, 2023)

Vulnerability and resilience of living marine resources to the Deepwater Horizon oil spill: an overview - Steven A. Murawski; Patrick T. Schwing; William F. Patterson; Tracey T. Sutton; Paul A. Montagna; Rosanna J. Milligan; Samantha B. Joye; Len Thomas; Joshua P. Kilborn; Claire B. Paris; Robin Faillettaz; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The 2010 Deepwater Horizon (DWH) oil well blowout in the Gulf of Mexico (GoM) was the largest and perhaps most consequential accidental marine oil spill in global history. This paper provides an overview of a Research Topic consisting of four additional papers that: (1) assemble time series data for ecosystem components in regions impacted by the spill, and (2) interpret temporal changes related to the vulnerability of species and ecosystems to DWH and the ensuing resilience to perturbation. Time series abundance data for many taxa pre-date DWH, often by decades, thus allowing an assessment of population- and community-level impacts. We divided the north central GoM into four interconnected “eco-types”: the coastal/nearshore, continental shelf, open-ocean pelagic and deep benthic. Key taxa in each eco-type were evaluated for their vulnerability to the circumstances of the DWH spill based on population overlap with oil, susceptibility to oil contamination, and other factors, as well their imputed resilience to population-level impacts, based on life history metrics, ecology and post-spill trajectories. Each taxon was scored as low, medium, or high for 13 vulnerability attributes and 11 resilience attributes to produce overall vulnerability and resilience scores, which themselves were also categorical (i.e., low, medium, or high). The resulting taxon-specific V-R scores provide important guidance on key species to consider and monitor in the event of future spills similar to DWH. Similar analyses may also guide resource allocation to collect baseline data on highly vulnerable taxa or those with low resilience potential in other ecosystems. For some species, even a decade of observation has been insufficient to document recovery given chronic, long-term exposure to DWH oil remaining in all eco-types and because of impacts to the reproductive output of long-lived species. Due to the ongoing threats of deep-water blowouts, continued surveillance of populations affected by DWH is warranted to document long-term recovery or change in system state. The level of population monitoring in the open-ocean and deep benthic eco-types has historically been low and is inconsistent with the continued migration of the oil industry to the ultra-deep (≥1,500 m) where the majority of leasing, exploration, and production now occurs.

A global assessment of the prevalence of current and potential future infrastructure in Key Biodiversity Areas - Ashley T. Simkins; Alison E. Beresford; Graeme M. Buchanan; Olivia Crowe; Wendy Elliott; Pablo Izquierdo; David J. Patterson; Stuart H.M. Butchart (Biological Conservation, 2023)

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

The bioeconomic paradox of market-based invasive species harvest: a case study of the commercial lionfish fishery - Holden E. Harris; William F. Patterson; Robert N. M. Ahrens; Micheal S. Allen; David D. Chagaris; Sherry L. Larkin (Biological Invasions, 2023)

Three trap designs evaluated for a deepwater lionfish fishery - Holden E. Harris; Steven B. Garner; Joseph H. Tarnecki; Stephen R. Gittings; David D. Chagaris; William F. Patterson (Frontiers in Marine Science, 2023)
A deepwater (>40 m) fishery for invasive lionfish ( Pterois volitans/miles ) offers a potential means to control invasive lionfish densities and mitigate their impacts on reefs too deep for SCUBA removals. Trapping could provide a scalable solution—if an effective fishing gear with minimal environmental impacts could be permitted and adopted by fishers. We tested the efficacy of wooden slat lobster traps, wire sea bass traps, and experimental non-containment Gittings traps. One hundred deployments of each trap type were made at 120 mesophotic (38–78 m deep) natural reef sites in the northeastern Gulf of Mexico (29.6–30.1°N, 86.1–87.6°W). Reef sites were surveyed with remotely operated vehicles (ROV) before and after trap deployments, and remote time-lapse video cameras were affixed above 86 traps to sample in situ recruitment to the traps. The video data showed that lionfish were attracted to the vicinity of the three trap types at similar rates, but that lionfish rarely entered the lobster or sea bass traps. The high bycatch rates of sea bass traps suggested their use is likely unsuitable for targeting lionfish. Lobster traps had lower rates of bycatch, but their relatively high ratio of bycatch-to-lionfish catches suggests that modifications will be needed to make them more efficient. The Gittings traps had the highest lionfish catch rates and lowest bycatches of native fishes, but operational issues were also identified. They failed to open on 20% of deployments and one entangled a green sea turtle ( Chelonia mydas ). Even with the best-performing trap design, the average catch rate of lionfish was less than one lionfish per trap. A potential explanation could be the low biomass of lionfish observed during the ROV surveys, which averaged 0.3 kg lionfish per site. The time-lapse video data suggested that lionfish recruitment to Gittings traps could increase with higher densities of lionfish on the nearby reefs, if traps were retrieved after approximately two days of deployment, and if traps were retrieved during dawn or dusk. Further research, development, and testing is needed for lionfish traps, and critical bio- and techno-economic assessments appear warranted to evaluate the feasibility of a deepwater lionfish fishery.

Perceptions of Freshwater Algal Blooms, Causes and Health among New Brunswick Lakefront Property Owners - Sapriya Birk; J. David Miller; Aidan MacMullin; R. Timothy Patterson; Paul J. Villeneuve (Environmental Management, 2023)

Episodic Ataxia Type 1: Natural History and Effect on Quality of Life - Tracey D. Graves; Robert C. Griggs; Brian N. Bundy; Joanna C. Jen; Robert W. Baloh; Michael G. Hanna; Joanna J. Jen; Anthony A. Amato; Richard J. Barohn; Angelika F. Hahn; Kimberly Hart; Barbara Herr; et al. (The Cerebellum, 2022)
Episodic ataxia type 1 (EA1) is a rare autosomal potassium channelopathy, due to mutations in KCNA1 . Patients have childhood onset of intermittent attacks of ataxia, dizziness or imbalance. In order to quantify the natural history of EA1, its effect on quality of life and in preparation for future clinical trials, we set up an international multi-centre study of EA1. We recruited thirty-three participants with EA1: twenty-three completed 1-year follow-up and eighteen completed 2-year follow-up. There was very little accumulation of disability or impairment over the course of the 2 years of the study. The outcome measures of ataxia (SARA and functional rating of ataxia) and the activities of daily living scale were largely stable over time. Self-reported health-related quality of life (SF-36) scores were lower across all domains than controls, in keeping with a chronic condition. Physical subdomain scores appeared to deteriorate over time, which seems to be driven by the female participants in the study. This is an interesting finding and warrants further study. Attacks of EA1 reported by participants in real time via an interactive voice response system showed that symptoms were not stereotyped; however, attack duration and frequency was stable between individuals. This large prospective study is the first ever completed in subjects with EA1. We document the natural history of the disorder over 2 years. These data will enable the development of outcome measures for clinical trials of treatment.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Effects of short-term decomposition on isotope values of fish tissues under natural conditions - Kathryn S. Peiman; Hsien-Yung Lin; Michael Power; Scott G. Hinch; David A. Patterson; Steven J. Cooke (Aquatic Ecology, 2022)

Using an integrative research approach to improve fish migrations in regulated rivers: a case study on Pacific Salmon in the Seton River, Canada - Nolan N. Bett; Scott G. Hinch; Arthur L. Bass; Douglas C. Braun; Nicholas J. Burnett; Matthew T. Casselman; Steven J. Cooke; S. Matthew Drenner; Ahmed Gelchu; William L. Harrower; Roxx Ledoux; Andrew G. Lotto; et al. (Hydrobiologia, 2022)

Host‐pathogen‐environment interactions predict survival outcomes of adult sockeye salmon ( Oncorhynchus nerka ) released from fisheries - Amy K. Teffer; Scott G. Hinch; Kristina M. Miller; David. A. Patterson; Arthur L. Bass; Steven J. Cooke; Anthony P. Farrell; Terry D. Beacham; Jacqueline M. Chapman; Francis Juanes (Molecular Ecology, 2022)
Incorporating host‐pathogen(s)‐environment axes into management and conservation planning is critical to preserving species in a warming climate. However, the role pathogens play in host stress resilience remains largely unexplored in wild animal populations. We experimentally characterized how independent and cumulative stressors (fisheries handling, high water temperature) and natural infections affected the health and longevity of released wild adult sockeye salmon ( Oncorhynchus nerka ) in British Columbia, Canada. Returning adults were collected before and after entering the Fraser River, yielding marine‐ and river‐collected groups, respectively ( N = 185). Fish were exposed to a mild (seine) or severe (gill net) fishery treatment at collection, and then held in flow‐through freshwater tanks for up to four weeks at historical (14°C) or projected migration temperatures (18°C). Using weekly nonlethal gill biopsies and high‐throughput qPCR, we quantified loads of up to 46 pathogens with host stress and immune gene expression. Marine‐collected fish had less severe infections than river‐collected fish, a short migration distance (100 km, 5–7 days) that produced profound infection differences. At 14°C, river‐collected fish survived 1–2 weeks less than marine‐collected fish. All fish held at 18°C died within 4 weeks unless they experienced minimal handling. Gene expression correlated with infections in river‐collected fish, while marine‐collected fish were more stressor‐responsive. Cumulative stressors were detrimental regardless of infections or collection location, probably due to extreme physiological disturbance. Because river‐derived infections correlated with single stressor responses, river entry probably decreases stressor resilience of adult salmon by altering both physiology and pathogen burdens, which redirect host responses toward disease resistance.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Modification of the third phase in the framework for vertebrate species persistence in urban mosaic environments - Colleen T. Downs; Jarryd Alexander; Mark Brown; Moses Chibesa; Yvette C. Ehlers Smith; S. Thobeka Gumede; Lorinda Hart; Kyrone K. Josiah; Riddhika Kalle; Machawe Maphalala; Mfundo Maseko; Shane McPherson; et al. (Ambio, 2021)

Modification of the third phase in the framework for vertebrate species persistence in urban mosaic environments - Colleen T. Downs; Jarryd Alexander; Mark Brown; Moses Chibesa; Yvette C. Ehlers Smith; S. Thobeka Gumede; Lorinda Hart; Kyrone K. Josiah; Riddhika Kalle; Machawe Maphalala; Mfundo Maseko; Shane McPherson; et al. (Ambio, 2021)

Directed evolution of the B. subtilis nitroreductase YfkO improves activation of the PET-capable probe SN33623 and CB1954 prodrug - Michelle H. Rich; Abigail V. Sharrock; Amir Ashoorzadeh; Adam V. Patterson; Jeff B. Smaill; David F. Ackerley (Biotechnology Letters, 2021)

Uncovering ecological state dynamics with hidden Markov models - Brett T. McClintock; Roland Langrock; Olivier Gimenez; Emmanuelle Cam; David L. Borchers; Richard Glennie; Toby A. Patterson (Ecology Letters, 2020)
Ecological systems can often be characterised by changes among a finite set of underlying states pertaining to individuals, populations, communities or entire ecosystems through time. Owing to the inherent difficulty of empirical field studies, ecological state dynamics operating at any level of this hierarchy can often be unobservable or ‘hidden’. Ecologists must therefore often contend with incomplete or indirect observations that are somehow related to these underlying processes. By formally disentangling state and observation processes based on simple yet powerful mathematical properties that can be used to describe many ecological phenomena, hidden Markov models (HMMs) can facilitate inferences about complex system state dynamics that might otherwise be intractable. However, HMMs have only recently begun to gain traction within the broader ecological community. We provide a gentle introduction to HMMs, establish some common terminology, review the immense scope of HMMs for applied ecological research and provide a tutorial on implementation and interpretation. By illustrating how practitioners can use a simple conceptual template to customise HMMs for their specific systems of interest, revealing methodological links between existing applications, and highlighting some practical considerations and limitations of these approaches, our goal is to help establish HMMs as a fundamental inferential tool for ecologists.

Climate effects on size‐at‐age and growth rate of Chinook Salmon ( Oncorhynchus tshawytscha ) in the Fraser River, Canada - Yi Xu; A. Scott Decker; Charles K. Parken; Lynda M. Ritchie; David A. Patterson; Caihong Fu (Fisheries Oceanography, 2020)
Decline in size‐at‐age of Chinook Salmon ( Oncorhynchus tshawytscha ) has been observed for many populations across the entire Northeast Pacific Ocean, and identifying external drivers of this decline is important for sustainable management of these ecologically, economically, and culturally valuable resources. We assessed size‐at‐age of 96,939 Chinook Salmon sampled in the Fraser River watershed (Canada) from 1969 to 2017. A broad decline in size‐at‐age was confirmed across all population aggregates of Fraser River Chinook Salmon, in particular since year 2000. By developing a novel probability‐based approach to calculate age‐ and year‐specific growth rates for Fraser River Chinook Salmon and relating growth rates to environmental conditions in specific years through a machine learning method (boosted regression trees), we were able to disentangle multi‐year effects on size‐at‐age and thus identify environmental factors that were most related to the observed size‐at‐age of Chinook Salmon. Among 10 selected environmental variables, ocean salinity at Entrance Island in spring, the Aleutian Low Pressure Index and the North Pacific Current Bifurcation Index were consistently identified as important contributors for four of the seven age and population aggregate combinations. These top environmental contributors could be incorporated into future stock assessment and forecast models to improve Chinook Salmon fisheries management under climate change.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Relative Effects of Multiple Stressors on Reef Food Webs in the Northern Gulf of Mexico Revealed via Ecosystem Modeling - David D. Chagaris; William F. Patterson; Micheal S. Allen (Frontiers in Marine Science, 2020)

The effect of severe and moderate hypoxia on exercise at a fixed level of perceived exertion - Owen Jeffries; Stephen David Patterson; Mark Waldron (European Journal of Applied Physiology, 2019)

A synthesis to understand responses to capture stressors among fish discarded from commercial fisheries and options for mitigating their severity - Katrina V. Cook; Andrea J. Reid; David A. Patterson; Kendra A. Robinson; Jacqueline M. Chapman; Scott G. Hinch; Steven J. Cooke (Fish and Fisheries, 2019)
Discarding non‐target fish from commercial fisheries is controversial and has been a persistent concern for fisheries managers globally. Discard management strategies typically begin by understanding mortality rates among discarded fish, a challenging task given the dynamic, highly context‐specific nature of fisheries. An alternative is to develop our knowledge of how stressors operate by first understanding the causes of mortality that drive this context dependence. Particularly relevant to mitigation efforts is an understanding of how fish respond to the physical factors of fishing, such as the gear itself and methods of fishing and handling the gear. We provide a synthesis of how commercial fishing methods may influence discard mortality and outline means by which capture‐induced stress and injury can be mitigated for common commercial gear types, emphasizing method variants or alternatives during capture, handling, and release that could improve survival. This synthesis identifies exhaustion and injury as the most detrimental and ubiquitous stressors experienced by discarded fish, with few options for mitigating their effects. Trawls and hanging net fisheries are identified as the most harmful gears for by‐catch, characterized by high stress regardless of method variants and limited options for mitigation. Irrespective of gear type and type of stressor, minimizing durations of capture and handling and encouragement of good handling behaviour (e.g., during landing and sorting) will reduce the magnitude of stress and injury in fish, and ultimately increase survival.

Genotyping confirms significant cannibalism in northern Gulf of Mexico invasive red lionfish, Pterois volitans - Kristen A. Dahl; David S. Portnoy; J. Derek Hogan; John E. Johnson; John R. Gold; William F. Patterson (Biological Invasions, 2018)

Temporal and spatial differences in smolting among Oncorhynchus nerka populations throughout fresh and seawater migration - Marley C. Bassett; David A. Patterson; J. Mark Shrimpton (Journal of Fish Biology, 2018)
Physiological changes that occur in the spring are preparatory for salmonid smolts to successfully enter seawater, but variation is likely to exist within species with a wide geographic distribution. Whether differences in development of seawater tolerance exist among populations that differ in distance to the ocean, temporally during the spring, or as fish migrate downstream is not known. Juvenile sockeye salmon Oncorhynchus nerka from four regions in the Fraser River catchment, British Columbia, were intercepted to assess physiological differences among populations and at different times during migration to characterize the parr–smolt transformation. Pre‐migratory fish had low levels of gill Na + –K + ‐ATPase (NKA) activity. High gill NKA activities were observed at the start of migration for some populations, but smolts leaving the lake did not consistently have higher gill NKA activity than non‐migratory juvenile O. nerka sampled in their natal lakes. Gill NKA activity was highly variable at the start of migration with no relationship with distance from the ocean. Gill NKA activity changes with migration were also highly variable, but consistently smolts in the ocean had the highest enzyme activities. Internal and external factors may influence this variation, but the dynamic nature of smolting was not based on the region of origin, timing during migration or on the year of migration.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Evaluating Current Practices in Shelf Life Estimation - Robert Capen; David Christopher; Patrick Forenzo; Kim Huynh-Ba; David LeBlond; Oscar Liu; John O’Neill; Nate Patterson; Michelle Quinlan; Radhika Rajagopalan; James Schwenke; Walter Stroup (AAPS PharmSciTech, 2018)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Growth and biochemical responses of Skeletonema costatum to petroleum contamination - James L. Wee; David F. Millie; Ngan K. Nguyen; Johnathan Patterson; Rose Ann Cattolico; David E. John; John H. Paul (Journal of Applied Phycology, 2016)

Effects of experimentally elevated egg cortisol on offspring traits in two species of wild Pacific salmon - Natalie M. Sopinka; Scott G. Hinch; Stephen J. Healy; Graham D. Raby; David A. Patterson (Environmental Biology of Fishes, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

IAEA Isotope-enabled coupled catchment–lake water balance model, IWBMIso: description and validation - Dagnachew Legesse Belachew; George Leavesley; Olaf David; Dave Patterson; Pradeep Aggarwal; Luis Araguas; Stefan Terzer; Jack Carlson (Isotopes in Environmental and Health Studies, 2016)

Using watershed characteristics to inform cost-effective stream temperature monitoring - Douglas C. Braun; John D. Reynolds; David A. Patterson (Aquatic Ecology, 2015)

Environmental conditions and physiological state influence estuarine movements of homing sockeye salmon - S. Matthew Drenner; Scott G. Hinch; Eduardo G. Martins; Nathan B. Furey; Timothy D. Clark; Steven J. Cooke; David A. Patterson; David Robichaud; David W. Welch; Anthony P. Farrell; Richard E. Thomson (Fisheries Oceanography, 2015)
The reproductive migration of anadromous salmonids through estuarine waters is one of the most challenging stages of their life cycle, yet little is known about the environmental and physiological conditions that influence migratory behaviour. We captured, sampled tissues, tagged and released 365 sockeye salmon ( Oncorhynchus nerka ) homing through inner coastal waters towards the Fraser River, British Columbia, Canada. Biotelemetry was used to assess the behaviour of individual sockeye salmon approaching estuarine waters and at river entry, which were related to both fish physiological condition at release and to prevailing environmental conditions. Sockeye salmon tended to stay close to the shore, migrated during the day, and movements were related to tide. Sockeye salmon migration rate was linked to wind‐induced currents, salinity and an individual's physiological state, but these factors were specific to location and stock. We propose that wind‐induced currents exposed sockeye salmon entering the estuary to stronger olfactory cues associated with Fraser River water, which in turn resulted in faster migration rates presumably due to either an increased ability for olfactory navigation and/or advanced reproductive schedule through a neuroendocrine response to olfactory cues. However, once the migration had progressed further into more concentrated freshwater of the river plume, sockeye salmon presumably used wind‐induced currents to aid in movements towards the river, which may be associated with energy conservation. Results from this study improve our biological understanding of the movements of Fraser River sockeye salmon and are also broadly relevant to other anadromous salmonids homing in marine environments.

Superresolution imaging of viral protein trafficking - Anamaris M. Colberg-Poley; George H. Patterson; Kyle Salka; Shivaprasad Bhuvanendran; David Yang; Jyoti K. Jaiswal (Medical Microbiology and Immunology, 2015)

Climate change implications in the northern coastal temperate rainforest of North America - Colin S. Shanley; Sanjay Pyare; Michael I. Goldstein; Paul B. Alaback; David M. Albert; Colin M. Beier; Todd J. Brinkman; Rick T. Edwards; Eran Hood; Andy MacKinnon; Megan V. McPhee; Trista M. Patterson; et al. (Climatic Change, 2015)

Erratum to: Magnitude and Trophic Fate of Black Needlerush (Juncus Roemerianus) Productivity: Does Nutrient Addition Matter? - Amy Hunter; Just Cebrian; Jason P. Stutes; David Patterson; Bart Christiaen; Celine Lafabrie; Josh Goff (Wetlands, 2015)

Magnitude and Trophic Fate of Black Needlerush (Juncus Roemerianus) Productivity: Does Nutrient Addition Matter? - Amy Hunter; Just Cebrian; Jason P. Stutes; David Patterson; Bart Christiaen; Celine Lafabrie; Josh Goff (Wetlands, 2015)

Emergent stability in a large, free‐flowing watershed - Jonathan W. Moore; Michael P. Beakes; Holly K. Nesbitt; Justin D. Yeakel; David A. Patterson; Lisa A. Thompson; Corey C. Phillis; Douglas C. Braun; Corinna Favaro; David Scott; Charmaine Carr-Harris; William I. Atlas (Ecology, 2015)
While it is widely recognized that financial stock portfolios can be stabilized through diverse investments, it is also possible that certain habitats can function as natural portfolios that stabilize ecosystem processes. Here we propose and examine the hypothesis that free‐flowing river networks act as such portfolios and confer stability through their integration of upstream geological, hydrological, and biological diversity. We compiled a spatially (142 sites) and temporally (1980–present) extensive data set on fisheries, water flows, and temperatures, from sites within one of the largest watersheds in the world that remains without dams on its mainstem, the Fraser River, British Columbia, Canada. We found that larger catchments had more stable fisheries catches, water flows, and water temperatures than smaller catchments. These data provide evidence that free‐flowing river networks function as hierarchically nested portfolios with stability as an emergent property. Thus, free‐flowing river networks can represent a natural system for buffering variation and extreme events.

The effects of massed versus distributed contractions on the variability of maximal isometric force - Jessica McGuire; Lara Green; Kristina Calder; Jae Patterson; David A. Gabriel (Experimental Brain Research, 2014)

Prostate specific membrane antigen produces pro-angiogenic laminin peptides downstream of matrix metalloprotease-2 - Rebecca E. Conway; Kyle Joiner; Alex Patterson; David Bourgeois; Robert Rampp; Benjamin C. Hannah; Samantha McReynolds; John M. Elder; Hannah Gilfilen; Linda H. Shapiro (Angiogenesis, 2013)

Valuation of National Park System Visitation: The Efficient Use of Count Data Models, Meta-Analysis, and Secondary Visitor Survey Data - Christopher Neher; John Duffield; David Patterson (Environmental Management, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Climate effects on growth, phenology, and survival of sockeye salmon (Oncorhynchus nerka): a synthesis of the current state of knowledge and future research directions - Eduardo G. Martins; Scott G. Hinch; Steven J. Cooke; David A. Patterson (Reviews in Fish Biology and Fisheries, 2012)

On the Shelf Life of Pharmaceutical Products - Robert Capen; David Christopher; Patrick Forenzo; Charles Ireland; Oscar Liu; Svetlana Lyapustina; John O’Neill; Nate Patterson; Michelle Quinlan; Dennis Sandell; James Schwenke; Walter Stroup; et al. (AAPS PharmSciTech, 2012)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

The effects of experimental energy depletion on the physiological condition and survival of adult sockeye salmon (Oncorhynchus nerka) during spawning migration - Patrick S. Nadeau; Scott G. Hinch; Kimberly A. Hruska; Lucas B. Pon; David A. Patterson (Environmental Biology of Fishes, 2010)

Molecular genetic analysis of Down syndrome - David Patterson (Human Genetics, 2009)

Mapping and validation of quantitative trait loci for resistance to Cercospora zeae-maydis infection in tropical maize (Zea mays L.) - Gilberto Pozar; David Butruille; Heyder Diniz Silva; Zoe Patterson McCuddin; Julio Cesar Viglioni Penna (Theoretical and Applied Genetics, 2009)

Newer Technologies and Bioenergy Bring Focus Back to Bark Factor Equations - Paul F. Doruska; David Patterson; Jonathan Hartley; Matthew Hurd; Timothy Hart (Journal of Forestry, 2009)
Recent technological advances have made estimating outside bark, upper stem diameters on tree stems more commonplace. Inside bark diameters and bark thicknesses are also often needed at upper stem locations for volume determination applications, but those attributes are not easily measured, even with the newer technologies. Interest in bark and timber residue for bioenergy uses has also put increased focus on the ability to measure or estimate bark thickness at various heights aboveground. Bark factor (BF) equations allow one to estimate the ratio of inside bark diameter to outside bark diameter at a given height aboveground for a given tree. This ratio can then be multiplied by outside bark diameter measurements to yield estimates of inside bark diameters. Bark thickness can then be found via subtraction. This project developed BF equations for three hardwood species found in northwest Arkansas, nine hardwood species found in southeast Arkansas, and two hardwood species found in north central Wisconsin. Three distinct patterns in BF were observed, with the R2 of the fitted regression equations ranging from 0.76 to 0.97. Example applications are also described.

Jack Edgar Myers (1913–2006), an algal physiologist par excellence - Jerry J. Brand; David W. Krogmann; C. O. Patterson (Photosynthesis Research, 2008)

Phytoplankton-Group Specific Quantitative Polymerase Chain Reaction Assays for RuBisCO mRNA Transcripts in Seawater - David E. John; Stacey S. Patterson; John H. Paul (Marine Biotechnology, 2007)

Behaviour and physiology of sockeye salmon homing through coastal waters to a natal river - Glenn T. Crossin; Scott G. Hinch; Steven J. Cooke; David W. Welch; Sonia D. Batten; David A. Patterson; Glen Van Der Kraak; J. Mark Shrimpton; Anthony P. Farrell (Marine Biology, 2007)

The use of hydrologic and Ecological indicators for the restoration of drainage ditches and water diversions in a Mountain Fen, Cascade Range, California - Lindsay Patterson; David J. Cooper (Wetlands, 2007)

Susceptibility of imidacloprid-resistant Colorado potato beetles to non-neonicotinoid insecticides in the laboratory and field trials - Andrei Alyokhin; Galen Dively; Megan Patterson; Matthew Mahoney; David Rogers; John Wollam (American Journal of Potato Research, 2006)

Outside-Bark Green Tons per Thousand Board Feet: A Case Study Using Sawtimber-Sized Hardwood Trees in Arkansas - Paul Doruska; David Patterson; Jonathan Hartley; Matthew Hurd (Journal of Forestry, 2006)
Timber transactions have shifted from a volume basis to a weight basis over the last 40 years in much of the southeastern United States. This shift has posed problems when sawtimber inventories are conducted in terms of board feet and then converted to outside-bark green tons for valuation. This case study examines tons per thousand board feet conversion factors for the Doyle, Scribner, and International ¼ log rules for a collection of hardwood species in Arkansas. Conversion factors ranged from 20 tn/mbf Doyle to 5 tn/mbf Doyle as scaling diameters increased from 8 to 26 in. Conversion factors for the Scribner and International ¼ log rules varied from about 9 tn/mbf to about 5 tn/mbf over the same range in scaling diameters. Often, a single tons per mbf conversion factor is used for a given species class (i.e., pine, oak, … ) in a given region of the United States. Regardless of the region of the United States, tree species, or board foot log rule, the results of this case study suggest more appropriate conversion factors should be used.

Ted Puck and the Era of Somatic Cell Genetics - David Patterson (In Vitro Cellular & Developmental Biology - Animal, 2006)

Cytokine gene polymorphisms in ischaemic heart disease: investigation using family-based tests of association - Paul G. McGlinchey; Mark S. Spence; Chris C. Patterson; Adrian R. Allen; Gillian Murphy; David A. Savage; A. Peter Maxwell; Pascal P. McKeown (Journal of Molecular Medicine, 2004)

Uncontrolled manifold analysis of single trials during multi-finger force production by persons with and without Down syndrome - John P. Scholz; Ning Kang; David Patterson; Mark L. Latash (Experimental Brain Research, 2003)

Toward estimation of map accuracy without a probability test sample - Brian M. Steele; David A. Patterson; Roland L. Redmond (Environmental and Ecological Statistics, 2003)

Free-living heterotrophic euglenids from freshwater sites in mainland Australia - Sabrina Schroeckh; Won Je Lee; David J. Patterson (Hydrobiologia, 2003)

Finger coordination in persons with Down syndrome: atypical patterns of coordination and the effects of practice - Mark L. Latash; Ning Kang; David Patterson (Experimental Brain Research, 2002)

Taking varves to bits: Scanning electron microscopy in the study of laminated sediments and varves - Jean M. Dean; Alan E.S. Kemp; David Bull; Jennifer Pike; Gunilla Patterson; Bernd Zolitschka (Journal of Paleolimnology, 1999)

A comparative analysis of nested subset patterns of species composition - David H. Wright; Bruce D. Patterson; Greg M. Mikkelson; Alan Cutler; Wirt Atmar (Oecologia, 1997)

Mapping of bovine PRGS and PAIS genes in hybrid somatic cells: Syntenic conservation with human chromosome 21 - James C. McAvin; David Patterson; James E. Womack (Biochemical Genetics, 1988)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Biochemical genetics of Chinese hamster cell mutants with deviant purine metabolism. VI. Enzymatic studies of two mutants unable to convert inosinic acid to adenylic acid - Alice S. Tu; David Patterson (Biochemical Genetics, 1977)

Use of exhaustive nucleic acid hybridization for determining the amount and size distribution of newly synthesized bacterial message RNA - David Gillespie; Allan Jacobson; Sally Gillespie; David Patterson (Biochemical Genetics, 1973)

Deductive analysis of a protein-synthesis mutant of Escherichia coli - David Patterson; David Gillespie (Biochemical Genetics, 1973)

A new RNA synthesis mutant of E. coli - David Patterson; Mark Weinstein; Sergio Marshall; David Gillespie (Biochemical Genetics, 1971)